2013
DOI: 10.1038/nature11867
|View full text |Cite
|
Sign up to set email alerts
|

Finding the sources of missing heritability in a yeast cross

Abstract: For many traits, including susceptibility to common diseases in humans, causal loci uncovered by genetic mapping studies explain only a minority of the heritable contribution to trait variation. Multiple explanations for this “missing heritability” have been proposed1. Here we use a large cross between two yeast strains to accurately estimate different sources of heritable variation for 46 quantitative traits and to detect underlying loci with high statistical power. We find that the detected loci explain near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
683
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(718 citation statements)
references
References 49 publications
28
683
6
1
Order By: Relevance
“…Our results complement one such study that recovered the chromosomal determinants accounting for almost all of the additive portion of heritability of several traits by dramatically expanding study sizes (4). In this previous study, potentially confounding nonchromosomal effects were mitigated by standardizing on a single mitochondrial background and by using only dsRNA virus-free strains (Supporting Information, Note 2, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Our results complement one such study that recovered the chromosomal determinants accounting for almost all of the additive portion of heritability of several traits by dramatically expanding study sizes (4). In this previous study, potentially confounding nonchromosomal effects were mitigated by standardizing on a single mitochondrial background and by using only dsRNA virus-free strains (Supporting Information, Note 2, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Despite the challenges in estimation, thousands of QTL have been found and many findings of interaction effects reported in crosses of divergent lines of chicken (Pettersson et al 2011), yeast (Bloom et al 2013), and Drosophila (Huang et al 2012. Further, there is recent evidence of detection of epistatic loci for levels of gene expression in human populations (Hemani et al 2014;Brown et al 2014).Nevertheless the variation contributed by these epistatic loci detected in segregating populations is generally found to be small (Huang et al 2012;Brown et al 2014;Hemani et al 2014), which fits with the theoretical predictions (Hill et al 2008) that only at high heterozygosity levels do loci contribute much epistatic variance; Bloom et al (2013) note that the epistatic variance they found would have been much lower had they not been using an F1-based population.The genetic variation accounted for by significant SNPs in genome-wide association studies (GWAS) in humans for both metric traits such as height and for multifactorial disease traits has typically been substantially less than the estimates of the additive genetic variation found in conventional pedigreebased quantitative genetic analyses. For example, the top 150 loci identified by SNPs account for only 10% of the variance in human height (Lango-Allen et al 2010).…”
supporting
confidence: 72%
“…Significance was determined using a Wilcoxon rank sum test. *P < 0.01; **P < 0.001; ***P < 0.0001. effects across environments (65), and the interactions between or within loci (70).…”
Section: Discussionmentioning
confidence: 99%